CHATBOTS AS A TOOL FOR PROMOTING STUDENT MENTAL HEALTH The following are the names of the children of the most beautiful and most beautiful women - Sukriyah, Toyyibatul Mukminatus; Jaannah, Ulfa Qomariatul; Husna, Fatimatul; Rifa’i, Moh (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The mental health of university students has increasingly become a global concern due to academic pressures, social challenges, and personal stress. Many students face barriers to accessing traditional mental health services, such as stigma, cost, and limited resources. In this context, this study highlights the potential of chatbots as an innovative tool to bridge gaps in mental health services within academic institutions.This research employs a qualitative approach with a case study design conducted at Nurul Jadid University. Data were collected through observations, interviews, and documentation to gain an in-depth understanding of the impact of chatbot usage on students' mental health. The respondents were students and lecturers, providing diverse perspectives on chatbot utilization. Data analysis involved reduction, presentation, and verification using content, discourse, and interpretive analysis methods. The findings indicate that chatbots are effective in addressing mild to moderate mental health issues but remain limited in handling more complex problems. A lack of personalization also emerged as a significant concern, with 55% of students and 60% of practitioners suggesting that improvements in this area are necessary to optimize the chatbot's ability to meet users' needs.